2014
DOI: 10.1055/s-0034-1375963
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Induced Nodular Regenerative Hyperplasia

Abstract: Drug-induced nodular regenerative hyperplasia is an uncommon injury with unique pathophysiology, clinical, and diagnostic considerations. This injury is characteristically asymptomatic in its early phases with only mild elevations in transaminases (< 3× upper limit of normal [ULN]). The latency period is typically more than 6 months. Once clinically apparent, it is marked by complications of portal hypertension, including hypersplenism, ascites, and variceal bleeding, with little or no hepatic dysfunction. Hen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 26 publications
0
39
0
Order By: Relevance
“…In the current study, we found a good correlation between LSM and HVPG that is likely indicative of the severity of NRH and underlying portal hypertension. It is therefore conceivable that early in the course of NRH, the HVPG may be low primarily due to presinusoidal portal hypertension . It is also possible that the variation in LSM in NRH is reflective of the predominant mechanism of injury (i.e., low LSM in presinusoidal versus high LSM in sinusoidal portal hypertension) .…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, we found a good correlation between LSM and HVPG that is likely indicative of the severity of NRH and underlying portal hypertension. It is therefore conceivable that early in the course of NRH, the HVPG may be low primarily due to presinusoidal portal hypertension . It is also possible that the variation in LSM in NRH is reflective of the predominant mechanism of injury (i.e., low LSM in presinusoidal versus high LSM in sinusoidal portal hypertension) .…”
Section: Discussionmentioning
confidence: 99%
“…NRH is characterized by widespread transformation of nor mal liver parenchyma into hyperplastic regenerative nodules without bridging fibrosis, a characteristic that distinguishes this entity from liver cirrhosis (15). This injury is characteristically asymptomatic in its early phases, with only mild elevations in transaminase levels (16). Ox aliplatin is a well-known causative drug for the development of NRH (17).…”
Section: Discussionmentioning
confidence: 99%
“…Nodular regenerative hyperplasia (NRH) may be present on a liver biopsy (Figure 1), but other times histology is unrevealing. Several medications including oral contraceptives, anti-neoplastic drugs and immunosuppressive agents have been implicated (27, 28). Due to the indolent development of portal hypertension from stellate cell stimulation and liver regeneration, latency periods can be long and well after drug discontinuance.…”
Section: Specific Chronic Injuriesmentioning
confidence: 99%